2018
DOI: 10.3390/genes9070325
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Gene Co-Expression Network Analysis Reveals Dysregulation of Mitochondrial Oxidative Phosphorylation in Eating Disorders

Abstract: The underlying mechanisms of eating disorders (EDs) are very complicated and still poorly understood. The pathogenesis of EDs may involve the interplay of multiple genes. To investigate the dysregulated gene pathways in EDs we analyzed gene expression profiling in dorsolateral prefrontal cortex (DLPFC) tissues from 15 EDs cases, including 3 with anorexia nervosa (AN), 7 with bulimia nervosa (BN), 2 AN-BN cases, 3 cases of EDs not otherwise specified, and 102 controls. We further used a weighted gene co-express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Also WGCNA method can group genes into the specified modules based on the high correlations between co-expression genes across the samples, resulting in a cluster of genes that share a similar function ( Langfelder and Horvath, 2008 ; Atila et al, 2009 ). Cumulative studies on the transcriptome data using the WGCNA method to investigate complex traits or disease in animals, such as obesity ( Kogelman et al, 2014 ), residual feed intake ( Kong et al, 2016 ), and fat deposition ( Oliveira et al, 2018 ), and in human, including brain evolution ( Oldham et al, 2006 ), schizophrenia ( Chang et al, 2017 ), autism ( Gupta et al, 2014 ), neuroblastoma ( Yang et al, 2018b ), and eating disorders ( Yang et al, 2018a ) has been reported. However, RNA-Seq has not been used to identify the candidate genes related to heat tolerance in buffaloes.…”
Section: Introductionmentioning
confidence: 99%
“…Also WGCNA method can group genes into the specified modules based on the high correlations between co-expression genes across the samples, resulting in a cluster of genes that share a similar function ( Langfelder and Horvath, 2008 ; Atila et al, 2009 ). Cumulative studies on the transcriptome data using the WGCNA method to investigate complex traits or disease in animals, such as obesity ( Kogelman et al, 2014 ), residual feed intake ( Kong et al, 2016 ), and fat deposition ( Oliveira et al, 2018 ), and in human, including brain evolution ( Oldham et al, 2006 ), schizophrenia ( Chang et al, 2017 ), autism ( Gupta et al, 2014 ), neuroblastoma ( Yang et al, 2018b ), and eating disorders ( Yang et al, 2018a ) has been reported. However, RNA-Seq has not been used to identify the candidate genes related to heat tolerance in buffaloes.…”
Section: Introductionmentioning
confidence: 99%
“…Weighted gene coexpression network analysis (WCGNA) was used to construct a coexpression network based on scale-free topology to detect coexpression modules of genes with similar patterns of expression (32). In our study, DEGs were input into the WGCNA package (v1.69) in R to construct weighted coexpression modules.…”
Section: Construction Of Gene Coexpression Networkmentioning
confidence: 99%
“…In the Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition), EDs primarily include anorexia nervosa (AN), bulimia nervosa (BN), binge eating disorders (BEDs), avoidant/restrictive food intake disorder (ARFID), ruminant/reflux disorders, and pica. In recent years, many studies on EDs have been published, such as epidemiological studies (e.g., Mitchison & Mond, 2015; Udo & Grilo, 2018), clinical medical studies (e.g., Yang et al, 2018), and psychological studies (e.g., Marzilli et al, 2018), which indicate that researchers have long been concerned about EDs. By summarizing and contextualizing the reviews of recent epidemiologic data on EDs in Asia and the Pacific, Thomas et al (2016) found that regions with EDs are transnational in distribution and that the prevalence rate of eating disorders is very high.…”
Section: Introductionmentioning
confidence: 99%